Gamification in EFL/ESL instruction: A systematic review of empirical research - Zhang, Songcun; Hasim, Zuwati (Frontiers in Psychology, 2023)
Introduction This systematic review aims to present the characteristics of the recent research in gamified EFL/ESL instruction, benefits and drawbacks of using gamification in EFL/ESL instruction, and gamification elements. Methods The researchers carried out database search in both Web of Science and the Scopus for relevant articles using 15 related key terms. Finally, forty journal articles aligned with the inclusion criteria. Results The results found that gamification has been widely utilized in more than ten non-English-speaking countries and various English language skills, which indicated that gamification has gained popularity in facilitating EFL/ESL learning. The benefits of using gamification included improving students’ English language skills and abilities, positively affecting students’ attitudes and emotional responses, providing an authentic language learning environment and cultivating students’ comprehensive competence. The drawbacks of using gamification mainly included the technical problems, short-lived positive effect, and the negative influence caused by the gamified competition, and so forth. The most frequently used gamification elements were feedback, points, quiz, digital badges, leaderboard, and reward, followed by progress bar, story-telling, challenge, videos, time limit, and competition. Discussion The results provide a better understanding of the state of using gamification in EFL/ESL instruction in recent years. It will be useful for researchers seeking to understand and evaluate gamification as well as to practitioners interested in using gamification.